RANCANG BANGUN ALAT SHUFFING DRING MENGGUNAKAN MOTOR DC SYSTEM KENDALI PULSE WIDTH MODULATION BERBASIS ARDUINO - wardiansyah putra; Nopriadi, Nopriadi (LPPM Universitas Putera Batam, 2022)
The rapid development of technology at this time can be seen along with the development of small entrepreneurs so that technological developments have an impact on human life, the sales method requires the development of technology in electronics in the form of machines that can help human work so as to facilitate the process of making all small and medium businesses. As an example of the large development of electronic device technology such as the Arduino Uno R3, one of the technological tools that is very simple and easy to operate in the form of making mini tools can be called a microcontroller which functions to process simple programs such as C++ programming and Arduino ID programming to drive a computer. The object that is connected to the Arduino Uno R3 to run perfectly also requires a PWM that can control a DC motor that can rotate left and right to rotate in the manufacture of shuffing dring drinks, which are better known as hot drinks, for example bandrek, the egg. The shuffing dring can also be referred to as a hot drink shaker, the existence of this shuffing dring drink can make it easier to manufacture so you don't have to wait a long time in making it, just enter the ingredients you want to eat in a short period of time, you can finish quickly how the arduino tool works. the code to pwm after that pwm itself drives the dc motor with the maximum possible rotation, it can also rotate in two directions in seconds so that the work is simpler to have two dc motors as drivers with the dc motor position from above rotating in two directions while the dc motor from below enough with one direction of rotation so that in the manufacturing process it is perfect. The test can be seen to have one PWM (Pulse Width modulation) that can move two dc motors simultaneously in different directions - surgery to get the key code from an Arduino which processes the Arduino ID program to run the two objects so that it can provide maximum results to the user.